A Packaged and Reusable Hydrogel Strain Sensor with Conformal Adhesion to Skin for Human Motions Monitoring. Issue 6 (19th December 2021) - Zhao, Meijin; Zhang, Wenshuai; Wang, Dan; Sun, Peipei; Tao, Yuanyuan; Xu, Lingxiao; Shi, Lei
Abstract: Flexible strain sensors based on conductive hydrogels show great potential in wearable devices, electronic skins, and bioelectronics. However, hydrogels inevitably exhibit poor durability for long‐term usage due to the water loss by evaporation. Herein, an external packaging strategy is demonstrated for fabricating sandwich‐like packaged hydrogel strain sensors (PHSSs) through the combination of conductive hydrogel injection and subsequent packaging via a photopolymerization procedure. The as‐prepared PHSS consists of two functional parts, internal hydrogel conducting wires exhibiting excellent linear strain sensing performance as sensing element and an external packaging hydrogel layer with good transparency and conformal adhesion to human skin. Thanks to these intriguing merits, the PHSS possesses the capability to detect both the large‐scale and subtle human motions precisely. Particularly, compared to conventional naked hydrogel strain sensors, the lifespan of PHSS is proved to be remarkably enlarged benefiting from the protective effect of external packaging layer towards the embedded hydrogel sensing element. Besides, the swelling property of external packaging layer even after severe dehydration enables the sensor to be reusable. This work provides a new approach for the fabrication of flexible strain sensors with enhanced lifespan and good reusability. Abstract : A packaged hydrogel strain sensor consisting of embedded conducting sensing elements and an external packaging layer is proposed. The excellent linear sensing property, good transparency, and conformal adhesion to human skin enable its capability to accurately monitor human motions. Benefiting from the external packaging strategy, the sensor exhibits a remarkably enlarged lifespan and good reusability.